Inverted Classroom in Self-regulated Learning during the Covid-19 Pandemic in University Students - Chumacero Calle, Juan Carlos (2022)
The year 2020, the Peruvian authorities decreed the development of virtual learning in universities, due to the appearance of the pandemic that originated the COVID.19, in order to avoid the increase of contagions, it is this context that the higher housesof study should, implemented strategies to improve the performance academice of the students, being one of them the use of the inverted classroom, the objective of this study was to demonstrate that the use of the Inverted Classroom significantly influences the self-regulated learning during the pandemic of the COVID-19. The method used was quantitative, basic, with a quasi-experimental design, applying a program to second cycle students of a public university. From the statistical processing it was possible to conclude that the inverted classroom significantly influences self-regulated learning.